Sistem Informasi Penggajian Pegawai Kecamatan Geneng Kabupaten Ngawi - Arif Setyawan - Universitas Surakarta; Joko Wandyatmono - Universitas Surakarta (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2017)
ABSTRACT : District of Geneng of Sub-Province Ngawi consists of eighteen countryside. Apart thecountryside governance with the sub-province about ten kilo meters. This area has temperature ofbetween 260 C- 360 C. Wide of region of District Geneng 87.04 km2 with amount resident 89.663head. Resident living in region of District Geneng most is farmer. Office of Governance of DistrictGeneng occupies the farm of property of government for the width of 1.919 m2 broadly building 1.204m2. District officer of counted 27 people, consisted of the faction III are nine people, faction II are threeof compassion of people and faction I of[is five of people.Writer perform research in District Geneng as a mean to deepen farther about remuneration serviceand also wish to know the problems that happened [in] the institution, besides also aim to fulfill someof pass conditions which have been specified by University Surakarta. Having taken steps of Researchhence writer can find the problem faced by the institution that is about difficulty in tracing identity ofofficer and difficulty in searching remuneration data. Therefore writer design the information systememploy the officer to overcome the problem. Research method which writer use method of bookstudies, observation, interview and analyzes.This report is limit at scheme of information system remuneration covering: making DFD, databasescheme, flowchart and input scheme and also output. System scheme aim to facilitate in applicationmaking in fact.After perceiving scheme of information system which have been made by a writer can take theconclusion that with the existence of system scheme, hence application making which in fact will easyto executed. As for database designed is officer database, database of remuneration and intakedatabase employ. Hereinafter using Visual Basic or Visual Foxpro can use scheme of informationsystem of remuneration in District Geneng in making of Remuneration application in District of Genengof Sub-Province Ngawi.Kata kunci: Informationsi system remuneration the officer.